Induction of Trained Immunity Protects Neonatal Mice Against Microbial Sepsis by Boosting Both the Inflammatory Response and Antimicrobial Activity - Zhou H; Lu X; Huang J; Jordan P; Ma S; Xu L; Hu F; Gui H; Zhao H; Bai Z; Redmond HP; Wang JH; et al. (Dove Medical Press, 2022)
Huiting Zhou,1,* Xiaying Lu,2,3,* Jie Huang,1,* Patrick Jordan,2 Shurong Ma,1 Lingqi Xu,1 Fangjie Hu,1 Huan Gui,1 He Zhao,1 Zhenjiang Bai,1 H Paul Redmond,2 Jiang Huai Wang,2 Jian Wang1 1Institute of Pediatric Research, Children's Hospital of Soochow University, Suzhou, People's Republic of China; 2Department of Academic Surgery, University College Cork, Cork University Hospital, Cork, Ireland; 3Department of Physiology, Gannan Medical University, Ganzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Jian Wang, Institute of Pediatric Research, Children's Hospital of Soochow University, Suzhou, People's Republic of China, Email wj196312@vip.163.com Jiang Huai Wang, Department of Academic Surgery, University College Cork, Cork University Hospital, Cork, Ireland, Email jh.wang@ucc.ieBackground: Neonates are susceptible to a wide range of microbial infection and at a high risk to develop severe sepsis and septic shock. Emerged evidence has shown that induction of trained immunity triggers a much stronger inflammatory response in adult monocytes/macrophages, thereby conferring protection against microbial infection.Methods: This study was carried out to examine whether trained immunity is inducible and exerts its protection against microbial sepsis in neonates.Results: Induction of trained immunity by Bacillus Calmette-Guerin (BCG) plus bacterial lipoprotein (BLP) protected neonatal mice against cecal slurry peritonitis-induced polymicrobial sepsis, and this protection is associated with elevated circulating inflammatory cytokines, increased neutrophil recruitment, and accelerated bacterial clearance. In vitro stimulation of neonatal murine macrophages with BCG+BLP augmented both inflammatory response and antimicrobial activity. Notably, BCG+BLP stimulation resulted in epigenetic remodeling characterized by histone modifications with enhanced H3K4me3, H3K27Ac, and suppressed H3K9me3 at the promoters of the targeted inflammatory and antimicrobial genes. Critically, BCG+BLP stimulation led to a shift in cellular metabolism with increased glycolysis, which is the prerequisite for subsequent BCG+BLP-triggered epigenetic reprogramming and augmented inflammatory response and antimicrobial capacity.Conclusion: These results illustrate that BCG+BLP induces trained immunity in neonates, thereby protecting against microbial infection by boosting both inflammatory and antimicrobial responses.Keywords: trained immunity, inflammatory response, antimicrobial activity, epigenetic reprogramming, intracellular metabolic rewiring, neonatal sepsis